A new parameter to characterize the charge transport regime in Ni/HfO2/Si-n+-based RRAMs. (April 2016) - Villena, M.A.; Roldán, J.B.; González, M.B.; González-Rodelas, P.; Jiménez-Molinos, F.; Campabadal, F.; Barrera, D.
Highlights: A new parameter to characterize electron transport in RRAMs has been introduced. The reset voltage can be estimated by using the threshold voltage for reset. An extraction technique has been proposed to extract easily the new parameter. A complete physical study has been developed to study the new parameter meaning. Abstract: In this work, a new parameter is defined to describe the charge transport regime and to understand the physics behind the operation of Ni/HfO2 /Si-n + -based RRAMs. An extraction process of the parameter from experimental reset I – V curves is proposed. The new parameter allows to know the relative importance of the two main transport mechanisms involved in the charge conduction in the low resistance state of the device: a tunneling current through a potential barrier and an ohmic component. A complete simulation study on this issue is provided. Furthermore, the reset voltage can be estimated using this new parameter.